MEDIA PEMBELAJARAN BERUPA VLOG EDUKASI BERBASIS YOUTUBE KIDS PADA MATERI SEJARAH PERJUANGAN PAHLAWAN DI LINGKUNGAN SEKITAR KELAS VI SD - Alena, Mareta; Faizal Chan; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop an educational vlog learning media based on YouTube Kids for the topic of local heroes’ historical struggles in sixth-grade elementary school. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included one teacher and 20 sixth-grade students at SDN 80/1 KM 3 Muara Bulian. The research instruments consisted of observation sheets, interviews, expert validation questionnaires, and teacher and student response questionnaires. Data were analyzed descriptively using percentage calculations to determine the validity and practicality levels. The validation results showed an average percentage of 91.6%, categorized as very valid. The practicality test results indicated an average percentage of 92%, categorized as very practical. The developed educational vlog media increased students’ interest and participation in history learning. Therefore, this media is considered valid and practical as an innovative alternative for teaching social science in elementary schools.